The Role of Village Disaster Preparedness Teams (TSBD) in Engaging Vulnerable Groups for Tidal Flood Risk Reduction: A Case Study of Taman Ayu Village - Rizky, Wanda; Komalasari, Maya Atri; Awalia, Hafizah (Master's Program in Sociology, Faculty of Social and Political Sciences, Universitas Negeri Surabaya, 2026)
Vulnerable groups such as people with disabilities, the elderly, women, and communities with limited access often face greater risks when disasters occur. This study aims to analyze the role of the Village Disaster Preparedness Team (TSBD) in involving vulnerable groups in disaster risk reduction activities at the village level. Therefore, their involvement in the disaster management system is an important aspect in building community resilience. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews with VDRT members, village officials, and vulnerable groups, field observations, and analysis of village disaster documents. The results show that the VDRT plays an active role in involving vulnerable groups through various mechanisms, such as village discussion forums, direct invitations to disaster activities, and their involvement in the VDRT organizational structure. In addition, vulnerable groups are also involved in the process of preparing village disaster documents so that their needs and perspectives can be accommodated in disaster mitigation planning. The findings of this study indicate that the involvement of vulnerable groups is not only symbolic but also provides a space for participation that allows them to contribute according to their capacities and abilities.